Analyzing the infertility burden of polycystic ovarian syndrome in China: A comprehensive age-period-cohort analysis with future burden prediction (1990-2030) - DongYi Shen; Yang Wang; PanWei Hu; Cong Qi; Hong Yang (Taylor & Francis Group, 2024)
Objective Polycystic ovarian syndrome (PCOS) is a common but complex endocrine disorder widely linked to infertility and miscarriage. This study assessed the correlation between PCOS and infertility.Methods Using the latest data from the Global Burden of Disease 2019 database, we conducted an in-depth assessment of the disease burden attributed to PCOS in China. This analysis was performed using the joinpoint regression, age-period-cohort, and autoregressive integrated moving average (ARIMA) models.Results Between 1990-2019, an upward trend was observed in the age-standardized prevalence of PCOS-related female infertility in China. Joinpoint regression analysis revealed an increasing trend in the age-standardized prevalence of PCOS-related female infertility burden indicators as well as the average annual percentage change and annual percentage change across all age groups in China. In terms of the cohort effect, the period rate ratios associated with the age-standardized prevalence of PCOS-related infertility increased steadily over time. The ARIMA model predicted a relatively swift upward trend in the age-standardized prevalence of PCOS-related infertility in China from 2020-2030.Conclusion The age-standardized prevalence of PCOS-related female infertility in China has increased between 1990-2019. The ARIMA model predicted that the age-standardized prevalence of this disease may continue to increase over the next decade. This study can increase the public's attention, improve women's health awareness, and have a certain significance for reducing female infertility related to PCOS.